Flexible Film-Type Sensor for Electrochemical Measurement of Dopamine Using a Molecular Imprinting Method - Kishi, Takumi; Fujie, Toshinori; Ohta, Hiroyuki; Takeoka, Shinji (Frontiers in Sensors, 2021)
• Neurotransmitters, which are responsible for signal transduction of nerve cells in the brain, are linked to various emotions, behaviors, and brain diseases in our daily life, and by measuring neurotransmitters existing in the brain, it is thought that the data can greatly contribute to the progress of brain science. The purpose of this study is to develop a flexible thin film-type sensor which can measure dopamine (DA) selectively and sensitively by electrochemical measurement. The thin-film sensor was prepared by printing gold colloidal ink on a polyimide film having a thickness of 25 μm, which is the most flexible, while maintaining the buckling load (1 mN) required for inserting it into brain and an electrode (DA-PPy electrode) was prepared by electropolymerization of polypyrrole (PPy) using DA as a template. The flexural rigidity of this sensor was 4.3 × 10-3 nNm, which was the smallest of all existing neurotransmitter sensors. From examination of the electrode area, it was clarified that DA could be measured with good sensitivity if the electrode area was 0.5 mm2 or more. When a DA solution of 0-100 nM was measured using the PA-PPy electrode, the slope of calibration curve was about 3.3 times that of a bare PPy electrode as a negative control, indicating an improvement in sensitivity by the molecular imprinting with DA. The sensor was used to measure 0 -100 nM norepinephrine (NE) and serotonin (5-HT), and the slope of the DA calibration curve at 0.24 V was much greater than those of NE and 5-HT because the selectivity for DA was also improved by molecular imprinting.